Peran Kepala Sekolah Dalam Pengambilan Keputusan Pada Perencanaan di MTS Al-Munawaroh - Khoirul Muttaqin; Muhammad Syafi’i; Samiyah (Jurnal Pendidikan Dasar Islam, 2024)
This study aims to understand the role of school principals in decision-making for educational planning at MTs Al-Munawaro. Decision-making in educational planning is a crucial aspect that affects the quality and direction of educational policies in schools. Using a qualitative approach, this research explores the experiences, views, and perceptions of the principal and teachers in the decision-making process. The findings show that the principal begins the decision-making process by gathering accurate data on human resources, school facilities, and student academic performance. Subsequently, the principal evaluates various decision alternatives, considering the budget, short- and long-term needs, and stakeholder involvement. The decisions made include curriculum planning, improvement of learning facilities, and teacher professional development programs. Decision implementation is monitored through regular evaluation meetings and feedback from stakeholders. The study also identifies challenges in decision-making, such as budget limitations that impact planning. Overall, the decision-making process carried out by the school principal plays an important role in enhancing the quality of education at MTs Al-Munawaro, despite various challenges that need to be addressed.